2020
DOI: 10.1177/1747021820973661
|View full text |Cite
|
Sign up to set email alerts
|

Compound word frequency modifies the effect of character frequency in reading Chinese

Abstract: In two eye-tracking studies, reading of two-character Chinese compound words was examined. First and second character frequency were orthogonally manipulated to examine the extent to which Chinese compound words are processed via the component characters. In Experiment 1, first and second character frequency were manipulated for frequent compound words, whereas in Experiment 2 it was done for infrequent compound words. Fixation time and skipping probability for the first and second character were affected by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 54 publications
(114 reference statements)
4
19
0
Order By: Relevance
“…While the analytical processing is surely important and indispensable, it should also be noted that due to CSL learners’ limited knowledge of Chinese morphemes, it is difficult for them to decode word meanings in an analytical way ( Gong et al, 2020b ). The growing number of studies have also shown that learners recognize words holistically in reading (e.g., Chu and Leung, 2005 ; Liu et al, 2010 ; Cui et al, 2021 ), and lexical orthographic knowledge helps to predict students’ reading comprehension performance ( Leong et al, 2011 ). Therefore, we argued that lexical orthographic knowledge may play a vital role in CSL learners’ acquisition of reading comprehension skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the analytical processing is surely important and indispensable, it should also be noted that due to CSL learners’ limited knowledge of Chinese morphemes, it is difficult for them to decode word meanings in an analytical way ( Gong et al, 2020b ). The growing number of studies have also shown that learners recognize words holistically in reading (e.g., Chu and Leung, 2005 ; Liu et al, 2010 ; Cui et al, 2021 ), and lexical orthographic knowledge helps to predict students’ reading comprehension performance ( Leong et al, 2011 ). Therefore, we argued that lexical orthographic knowledge may play a vital role in CSL learners’ acquisition of reading comprehension skills.…”
Section: Discussionmentioning
confidence: 99%
“…Though arrayed in line, characters are with syntagmatic relations, rather than linearly related. Therefore, to process sentences, readers need to segment words in a string of characters, which requires word and word-constituent knowledge at both form and meaning levels ( Li et al, 2009 ; Li and Pollatsek, 2020 ; Cui et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, readers may actively use an upcoming character to “constrain” the likely identity of the upcoming word. Because characters that occur frequently in print also tend to occur in many different words, they provide little constraint to narrow down the possible identity of a word in which the characters are embedded, thereby slowing the word-identification process relative to words with low-frequency characters (e.g., Cui et al, 2021). This hypothesis was more formally implemented by X.…”
Section: The Chinese Writing Systemmentioning
confidence: 99%
“…The project is also supported by grants from the Australian Research Council Discovery Project (DP190100719), National Office for Philosophy and Social Sciences of China (16BYY071), Key Science and Technology Program of Henan Chinese raise the obvious question: What role does the processing of characters play in the identification of words? Although the word-frequency effect has been reliably observed in Chinese, suggesting that words are important functional units that are represented in the mental lexicon, reports of the character-frequency effect are inconsistent, making the role of characters and their possible status as functional units less clear (e.g., see Cui et al, 2021Cui et al, , 2013Ma et al, 2015;G. Yan et al, 2006;Yu et al, 2021).…”
mentioning
confidence: 99%